Autonomous driving with a focus on HMI for parallel parking maneuvers - Jan Leistner; Zuzana Radová; Petr Bouchner (Acta Polytechnica CTU Proceedings, 2024)
Autonomous vehicles remain a major topic in the automotive industry today, including assistance systems, cooperative communication, and other aspects that lead to full vehicle autonomy. This paper investigates vehicle autonomy with a focus on parking assistance. Along with a review of parking assistants, the paper presents a prototype parking assistant with an alternative distance display. The parking assistant prototype, compared to parking without an assistant and conventional parking assistant, was tested in a real-world experiment of a within-subjects study design. The user experience of the proposed distance representation was obtained, and the results indicated that the prototype parking assistant with an alternative distance display helps less experienced drivers get a better idea of the distance from the obstacle.